COMPARATIVE STUDY OF EMOTIONAL INTELLIGENCE OF SECONDARY SCHOOL STUDENTS - Kumar, Nitin; Singh, Rajkumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotional intelligence is an important skill that helps individuals understand, manage and use their own and others’ emotions. The study of emotional intelligence of students in schools is important from the point of view that it has a profound impact on their academic and social development. Emotional intelligence is extremely important for the overall development of students. It not only affects their academic performance, but also improves their social and mental health. Focusing on the development of emotional intelligence in schools can improve the overall well-being of students and prepare them to face various challenges in life. Findings from the research - No significant difference was found in the emotional intelligence of male and female students of secondary schools, No significant difference was found in the emotional intelligence of urban and rural students of secondary schools.